QSAR Analysis on Apigenin Derivative Compounds as Antioxidant Using Semiempirical Austin Model 1 - Mumpuni, Esti; Mulatsari, Esti (Asian Journal of Chemistry, 2017)
Quantitative structure-activity relationship (QSAR) analysis has been done on derivative compounds of apigenin. Apigenin is one of flavonoid group compound that potential as antioxidant. QSAR analysis was initiated by modelling the structures of compounds and calculating the descriptors of QSAR using Hyperchem software with semiempirical Austin Model 1 (AM 1) method. Determination of QSAR equation has been done using multilinear regression analysis method on one of the statistical data processing software. Of the 18 QSAR equation models, based on the value of R, R2, SE and F obtained 4 QSAR equation models that qualified. The best QSAR equation model determined through the process of validation of the test set compounds. The validation result showed that the best QSAR equation model of the following equation: –log IC50 = 10.035 + (0.997 HOMO energy) + (2.134 LUMO energy) + (-0.045 hydration energy) + (-0.056 log P) + (-0.341 Dipole) + (-3.552 atomic charge of C5) + (4.138 atomic charge of C5’) The results of predicted IC50 on 91 apigenin derivative suggest that the hydration 50 compounds have better biological activity as antioxidant than apigenin and the compound 3,3',6-triamine apigenin is a compound with the smallest predicted IC50 value (1.76 μM).